Design and Development of a Delta 3D Printer Using Salvaged E-Waste Materials. (27th November 2019) - Simons, Anthony; Avegnon, Kossi L. M.; Addy, Cyrus
Abstract : The next phase of industrialization in the world is the use of 3D printing technology. Various 3D printing technologies are employed all over the world and for different purposes, from 3D printed houses to 3D printed food nutrients. Printer movement is achieved by carriages moving in a clearly defined X, Y, and Z orientation. The 3D printer has a lower work rate; subsequently, many printouts consume a lot of time due to their complexity. This paper elaborates on the design and development of a faster and fixed build platform 3D printer (Delta 3D printer) using locally available materials and e-waste. The Delta 3D printer movement is faster with a stable bed. Printer movement is achieved using three vertical axes placed 120° apart. Accuracy and speed are achieved with the use of NEMA 17 stepper motors to drive the various carriages on the vertical axes. Design calculations show that the least force delivered by the stepper motor is 1.73 N which exceeds 0.8334 N, the weight of the load to be carried. Furthermore, a stepper motor must turn 80 steps (rotational motion) in order to achieve 1 mm advance (linear motion). This ensures a higher printout resolution. In place of traditional linear rails, locally sourced square pipes were adopted coupled with bearings and a 3D printed carriage support, and a relatively cheaper but stable linear rail was developed. The goal of this research was to develop an alternative easy-to-build Delta 3D printer using locally sourced materials. This goal of this research was achieved, and the developed prototype was test-run under load conditions. It is recommended that salvaged e-waste should be properly managed for easy acquisition.